An assessment of the supply chain management for agricultural products in Cambodia - Hin, Kosla; Lim, Siphat (Edelweiss Applied Science and Technology, 2024)
The primary objective of this research is to examine the supply chain management of cashew nuts, mangoes, and cassava in Cambodia. The findings indicate that Cambodian farmers predominantly rely on traditional methods for crop cultivation. A significant issue is their lack of adequate knowledge regarding the assessment and utilization of land quality, which results in both the quantity and quality of their crop yields falling short of acceptable standards. Consequently, this deficiency adversely affects the market prices of their produce. To address this knowledge gap, it is essential for relevant institutions, particularly the Ministry of Agriculture, Forestry and Fisheries, to offer training programs that focus on modern agricultural techniques aimed at enhancing both the quantity and quality of crop production. Additionally, the study highlights the absence of an institution dedicated to analyzing land types and quality in Cambodia. Moreover, the establishment of an effective irrigation system is crucial for the successful growth of crops.